Ozonized Saline Solution (O3SS): Scientific Foundations (Ozone Therapy Global Journal, 2016)
Ozone therapy is a technology that is currently being used to treat a variety of diseases, with a growing spread in the medical field.Given the decision passed by the Spanish regional health authorities of Catalonia and Madrid to assimilate the major autohemotherapy to a blood drawn and to apply it the Royal Decree (Real Decreto)1088/2005, this paper presents a bibliographic review on the ozonized saline solution as a valid alternative method of use in daily practice by the ozone therapist. At the same time taking into account the controversies that this method has raised, the scientific foundations of O3SS are analyzed, leading to the conclusion that is safe, effective, low cost and ease of application, and having a broad scientific support